PENGEMBANGAN SISTEM TRANSPORTASI MULTI MODA DALAM KERANGKA EFISIENSI LOGISTIK MASYARAKAT PULAU DI KABUPATEN PANGKEP PROVINSI SULAWESI SELATAN - Nur Syam AS (Teknosains, 2016)
Based on the research results, it appears that the development ofmultimodal transportation system in Pangkep within the framework oflogistik efficiency island communities to do with optimizing the utilization oflarge rivers that cross the territory Pangkep. The third river is the nationalroad network services, in addition is located adjacent to the vertices of theother transport, such as road transport terminals, ports and railway stationplan. The river dock location that is on one site with markets and shops willfacilitate the transport of goods and facilitate the public to transact theircatch in the territorial waters of the island.The development of multimodal transportation system in Pangkep is needed,in addition to the potential that surrounded him, also have barriers andproblems faced by the island community. The high price of goods on theisland due to the lack mode of transport that can be used by localcommunities in accordance with the movement of goods and capacity needs.Volume logistik needs of the island community based food standards, thusrequiring facilities more adequate transport services through the provisionof specialized vessels, ie vessels with a capacity of 350 DWT. This ship is atype of vessel that can be saved by the government as a ship pilot for remoteareas and islands (promote the trade ships and ships follow the trade). Thetransport system development course provides broad direction of regionaldevelopment that can improve the welfare of the people in the islandterritories Pangkep.